Synthesis and characterization of poly-L-lysine-grafted silica nanoparticles synthesized via NCA polymerization and click chemistry - Kar, Mrityunjov; Vijayakumar, P. S.; Bhagavatula L. V. Prasad; Sen Gupta, Sayam (Langmuir, 2010)
Polypeptide polymer-grafted silica nanoparticles are of considerable interest because the ordered secondary structure of the polypeptide grafts imparts novel functional properties onto the nanoparticle composite. The synthesis of poly-L-lysine-grafted nanoparticles would be of particular interest because the high density of cationic charges on the surface could lead to many applications such as gene delivery and antimicrobial agents. In this work, we have developed a ``grafting-to'' approach using a combination of NCA polymerization and ``click chemistry'' to synthesize poly-L-lysine-grafted silica nanoparticles with a high graft density of 1 chain/nm(2). The covalent attachment of poly-L-lysine to silica nanoparticles (PLL-silica) was confirmed using a variety of techniques such as C-13 CP MAS NMR, TGA, and IR. This methodology was then extended to graft poly-L-lysine-b-poly-L-leucine copolymer (PLL-b-PLLeu-silica) and poly-L-benzylglutamate (PLUG silica) onto silica nanoparticles. All of these polypeptide-grafted nanoparticles show interesting aggregation properties in solution. The efficacy of PLL-silica and PLL-h-PLLeu-silica as antimicrobial agents was tested on both gram-negative B. cull and grain-positive Bacillus subtilis.

Self-standing three-dimensional networks of nanoparticles with controllable morphology by dynamic templating of surfactant hexagonal domains - Sharma, Kamendra P.; Ganai, Anal Kumar; Sen Gupta, Sayam; Kumaraswamy, Guruswamy (Chemistry of Materials, 2011)
Assembly of nanoparticles into free-standing three-dimensional networks has implications for a wide range of applications. We show that dynamic templating of surfactant hexagonal domains is a facile technique to organize nanoparticles into a network of particulate strands. Dispersed particles (> 10 nm), independent of particle chemistry, assemble into networks, when the surfactant matrix cools into the hexagonal phase. We demonstrate assembly of inorganic, polymeric, and protein nanoparticles into networks. Where particle assembly is reversible, particles are coated with polymers that are subsequently cross-linked to stabilize the networks after surfactant removal. This technique involves near ambient temperatures and a benign water wash for template removal. The network mesh size can be varied from submicrometers to tens of micrometers by controlling the cooling rate. Particle networks can be flow-oriented prior to cross-linking, and interpenetrating networks can also be formed.
Keywords: hexagonal; macroporous; nanoparticle; self assembly; surfactant

Synthesis and characterization of poly-L-lysine grafted SBA-15 using NCA polymerization and click chemistry - Kar, Mrityunjoy; Malvi, Bharmana; Das, Anindita; Panneri, Suyana; Sen Gupta, Sayam (Journal of Materials Chemistry, 2011)
Poly-L-lysine (PLL) grafted ordered mesoporous material was prepared by a combination of NCA polymerization and click chemistry. Large pore SBA-15 with a mesopore diameter of similar to 12 nm was synthesized using a previously reported method. The surface of this SBA-15 material was modified with azidopropyl groups. This ``clickable'' SBA-15 was then reacted with an alkyne terminated poly-L-lysine synthesized by the ring-opening polymerization of 3-cbz-L-lysine NCA with N-TMS propargylamine as the initiator. This procedure allows grafting of a uniform polymer film with a high polymer loading. No appreciable pore blocking was observed upon grafting of PLL. No change in the periodic structure of the SBA-15 was observed throughout the grafting process. The SBA-15 PLL conjugate was characterized using (13)C and (29)Si NMR, XRD, FT-IR, N(2) adsorption-desorption and thermogravimetry. The results indicate that polypeptides can be easily grafted onto various ordered mesoporous materials by this ``grafting to'' methodology with accessible pores and high loadings of the polypeptide.

Synthesis of glycopolypeptides by the ring opening polymerization of O-glycosylated-alpha-amino acid N-carboxyanhydride (NCA) - Pati, Debasis; Shaikh, Ashif Y.; Hotha, Srinivas; Sen Gupta, Sayam (Polymer Chemistry, 2011)
The novel synthesis of O-glycosylated lysine-NCA from a stable glycosyl donor and a commercially available protected amino acid in very high yield is reported. These O-glycosylated lysine-NCA monomers underwent ring opening polymerization using simple primary amine initiators to form well defined, high molecular weight homoglycopolypeptides and diblock co-glycopolypeptides. The synthesis of azide labelled end functionalized glycopolypeptides and amphiphilic diblock copolypeptides is also reported. This methodology represents an easy and practical route to the synthesis of O-glycosylated polypeptides with 100% glycosylation.

Synthesis of poly-L-glutamic acid grafted silica nanoparticles and their assembly into macroporous structures - Kar, Mrityunjoy; Pauline, Minois; Sharma, Kamendra; Kumaraswamy, Guruswamy; Sen Gupta, Sayam (Langmuir, 2011)
Polypeptide-coated silica nanoparticles represent an interesting class of organic inorganic hybrids since the ordered secondary structure of the polypeptide grafts imparts functional properties to these nanoparticles. The synthesis of a poly-L-glutamic acid (PLGA) silica nanoparticle hybrid by employing N-carboxyanhydride (NCA) polymerization to synthesize the polypeptide chains and Cu catalyzed azide alkyne cycloaddition reaction to graft these chains onto the silica surface is reported. This methodology enables the synthesis of well-defined polypeptide chains that are attached onto the silica surface at high surface densities. The PLGA-silica conjugate particles are well dispersed in water, and have been thoroughly characterized using multinuclear (C-13, Si-29) solid state NMR, thermogravimetric analysis, Fourier transform infrared, dynamic light scattering, and transmission electron microscopy. The pH-dependent reversible aggregation of the PLGA-silica particles, driven by the change in PLGA structure, has also been studied. Preliminary results on the use of aqueous dispersions of silica-PLGA for the preparation of three-dimensional macroporous structures with oriented pores by ice templating methodology are also demonstrated. These macroporous materials, comprising a biocompatible polymer shell covalently attached to rigid inorganic cores, adopts an interesting lamellar structure with fishbone-type architecture.

Synthesis and self-assembly of glycopolypeptides - Pati, Debasis; Sen Gupta, Sayam (Abstracts of Papers of the American Chemical Society, 2012)

Synthesis of functional hybrid silica scaffolds with controllable hierarchical porosity by dynamic templating - Ganai, Anal Kumar; Kumari, Sushma; Sharma, Kamendra P.; Panda, Chakadola; Kumaraswamy, Guruswamy; Sen Gupta, Sayam (Chemical Communications, 2012)
We report a facile one-pot synthesis of hierarchically porous scaffolds, with independent control over nanoparticle mesoporosity and scaffold macroporosity. Our technique combines the chemistry of mesoporous silica nanoparticles with the control afforded by dynamic templating of surfactant mesophases. These materials are readily functionalizable and allow controllable spatial variation in macroporosity.

Synthesis of silk fibroin-glycopolypeptide conjugates and their recognition with lectin - Das, Soumen; Pati, Debasis; Tiwari, Neha; Nisal, Anuya; Sen Gupta, Sayam (Biomacromolecules, 2012)
Silk fibroin (SF), the natural fibrous protein created by the Bombyx mori silk worm, is being increasingly excellent mechanical strength, high oxygen/water permeability, excellent mechanical strength; high oxygen/water:permeability, and biocompatibility: :It is also well known that surface. modification of SF, With Organic ligands such as the extracellular protein :binding. Arg-Gly-Asp, (RGD) peptides:,: help adhesion and,proliferation. of cells better-a key; requirement for it to function as extracellular. matrices; In this, Work, We have conjugated synthetic glycopolypeptides (GPs) that were synthesized by controlled ring opening polymerization of alpha-manno-lys N-carboxyanhydrides (NCAs) onto SF by using Cu catalyzed click reaction to synthesize 1 a new hybrid :Material (SF GP), Which We believe will have :both the mechanical properties of native SF and the molecular recognition property of the carbohydrates in the GP. By controlling the :amount of GP grafted onto SF, we have made three SF GP conjugates that differ in their ability to assemble into films. SF GP conjugates having a very high content of GP formed completely water soluble brush like polymer that displayed very high affinity toward the lectin concanavalin-A (Con-A) Films cast from SF-GP conjugates using lower amounts of grafted GP were more stable in water, and the stability can be modulated by varying the amount of G grafted. The water insoluble film SF-GP(25) was also found to bind to fluorescently labeled Con A, as was seen by confocal microscopy Such SF-GP hybrid films may be useful as mimics of extracellular matrices for tissue engineering:

Synthesis and self-assembly of amphiphilic homoglycopolypeptide - Dhaware, Vinita; Shaikh, Ashif Y.; Kar, Mrityunjoy; Hotha, Srinivas; Sen Gupta, Sayam (Langmuir, 2013)
The synthesis of the amphiphilic homoglycopolypeptide was carried out by a combination of NCA polymerization and click chemistry to yield a well-defined Polypeptide having an amphiphilic carbohydrate on its side chain. The amphiphilicity of the carbohydrate was achieved by incorporation of an alkyl chain, at the C-6 position of the carbohydrate thus also rendering the homoglycopolypeptide amphiphilic. The homoglycopolypeptide formed multimicellar aggregates in water above a critical concentration of 0.9 mu M due to phase separation. The multimicellar aggregates were characterized by DLS, TEM, and AFM. It is proposed that hydrophobic interactions of the aliphatic chains at the 6-position of the sugar moieties drives the assembly of these rod-like homoglycopolypeptide into large;spherical aggregates. These multimicellar aggregates encapsulate both hydrophilic as well as hydrophobic dye as was confirmed by confocal microscopy. finally, amphiphilic random polypeptides containing 10% and 20% alpha-D-mannose in addition to glucose containing a, hydrophobic alkyl chain at its 6 position were synthesized by our methodology, and these polymers Were also found to assemble into spherical nanostructures. The spherical assemblies Of amphiphilic random glycopolypeptides containing 10% and 20% mannose were found to be surface bioactive and were found, to interact with the lectin Con-A.

Synthesis of end-functionalized phosphate and phosphonate-polypeptides by ring-opening polymerization of their corresponding N-carboxyanhydride - Das, Soumen; Kar, Mrityunjoy; Sen Gupta, Sayam (Polymer Chemistry, 2013)
Phosphopolypeptides provide an interesting biomimetic analog for phosphorylated proteins that are involved in biomineralization. We have developed a high yielding synthesis of cysteine-based phosphate and phosphonate N-carboxyanhydride (NCA) by using the thiol-ene coupling reaction. These phosphate and phosphonate NCA monomers underwent polymerization using simple primary amine initiators to form well defined homophosphopolypeptides. Using a bifunctional initiator we were able to install a ``clickable'' alkyne or azide group at the end of the polypeptide chain. We were also able to successfully synthesize fully water-soluble phosphonate based polypeptides by hydrolysis of the corresponding phosphonate ester groups in the polypeptide. These water-soluble phosphopolypeptides adopt a random coil conformation at physiological pH.

Soft colloidal scaffolds capable of elastic recovery after large compressive strains - Rajamanickam, Raja; Kumar, Sushma; Kumar, Deepak; Ghosh, Shankar; Kim, Jong Chul; Tae, Giyoong; Sen Gupta, Sayam; Kumaraswamy, Guruswamy (Chemistry of Materials, 2014)
Assemblies of inorganic or glassy particles are typically brittle and cannot sustain even moderate deformations. This restricts the use of such materials to applications where they do not experience significant loading or deformation. Here, we demonstrate a general strategy to create centimeter-size macroporous monoliths, composed primarily (>90 wt %) of colloidal particles, that recover elastically after compression to about one-tenth their original size. We employ ice templating of an aqueous dispersion of particles, polymer, and cross-linker such that cross-linking happens in the frozen state. This method yields elastic composite scaffolds for starting materials ranging from nanoparticles to micron-sized dispersions of inorganics or glassy lattices. The mechanical response of the monoliths is also qualitatively independent of polymer type, molecular weight, and even cross-linking chemistry. Our results suggest that the monolith mechanical properties arise from the formation of a unique hybrid microstructure, generated by cross-linking the polymer during ice templating. Particles that comprise the scaffold walls are connected by a cross-linked polymeric mesh. This microstructure results in soft monoliths, with moduli similar to O (10(4) Pa), despite the very high particle content in their walls. A remarkable consequence of this microstructure is that the monolith mechanical response is entropic in origin: the modulus of these scaffolds increases with temperature over a range of 140 K. We show that interparticle connections formed by cross-linking during ice templating determine the monolith modulus and also allow relative motion between connected particles, resulting in entropic elasticity.

Spectroscopic and reactivity comparisons of a pair of bTAML complexes with Fe-V=O and Fe-IV=O units - Pattanayak, Santanu; Jasniewsk, Andrew J.; Rana, Atanu; Draksharapu, Apparao; Singh, Kundan K.; Weitz, Andrew; Hendrich, Michael; Que, Lawrence, Jr.; Dey, Abhishek; Sen Gupta, Sayam (Inorganic Chemistry, 2017)
In this report we compare the geometric and electronic structures and reactivities of [Fe-V(O)](-) and [Fe-IV(O)](2-) species supported by the same ancillary nonheme biuret tetraamido macrocyclic ligand (bTAML). Resonance Raman studies show that the Fe-O vibration of the [Fe-IV(O)](2-) complex 2 is at 798 cm(-1), compared to 862 cm(-1) for the corresponding [Fe-V(O)](-) species 3, a 64 cm(-1) frequency difference reasonably reproduced by density functional theory calculations. These values are, respectively, the lowest and the highest frequencies observed thus far for nonheme high-valent Fe-O complexes. Extended X-ray absorption fine structure analysis of 3 reveals an Fe-O bond length of 1.59 angstrom, which is 0.05 angstrom shorter than that found in complex 2. The redox potentials of 2 and 3 are 0.44 V (measured at pH 12) and 1.19 V (measured at pH 7) versus normal hydrogen electrode, respectively, corresponding to the [Fe-IV(O)](2-)/[Fe-III(OH)](2-) and [Fe-V(O)](-)/[Fe-IV(O)](2-) couples. Consistent with its higher potential (even after correcting for the pH difference), 3 oxidizes benzyl alcohol at pH 7 with a second-order rate constant that is 2500-fold bigger than that for 2 at pH 12. Furthermore, 2 exhibits a classical kinteic isotope effect (KIE) of 3 in the oxidation of benzyl alcohol to benzaldehyde versus a nonclassical KIE of 12 for 3, emphasizing the reactivity differences between 2 and 3.

Synthesis of phospho-polypeptides via phosphate-containing N-carboxyanhydride: application in enzyme-induced self-assembly, and calcium carbonate mineralization - Mondal, Basudeb; Das, Soumen; Panda, Sidharth; Dutta, Tahiti; Sen Gupta, Sayam (ChemPlusChem, 2020)
An easy synthetic strategy was developed to synthesize the phosphate-functionalized amino acid N-carboxyanhydride (NCA), using simple primary amine initiators to obtain homo and block phospho-polypeptides with controlled molecular weight and molecular weight distribution. The methodology was extended to the synthesis of the end-functionalized homo polypeptides (15 to 50 repeat unit) and block co-polypeptides with PEG (0.7 K, 2 K, and 5 K) and glycopolypeptide (15-unit mannose glycopolypeptide) as one of the blocks. The deprotected fully water-soluble anionic phosphate-based polypeptides showed pH-dependent helical conformation with a helical content of 20 %, which further changed to beta-sheets upon addition of the enzyme alkaline phosphatase (ALP) due to dephosphorylation. The block co-polypeptide containing PEG as one of the blocks led to its self-assembly into colloidal structures, such as vesicles with a hydrodynamic diameter of similar to 250 nm, due to the formation of amphiphilic block co-polymer upon dephosphorylation. The nature of the colloidal structures formed can be temporally controlled by the extent of dephosphorylation. Finally, the phospho-polypeptides serve as a template for the mineralization of calcium carbonate with varying polymorphs and morphologies.
Keywords: Biomineralization; enzymes; phosphopolypeptides; Proteins; Self-assembly

Solvent-free hydroxylation of unactivated C-H bonds in small molecules and macromolecules by a Fe complex - Chatterjee, Debasmita; Sajeevan, Amritha; Jana, Sandipan; Birajdar, Rajkumar S.; Chikkali, Samir H.; Sivaram, Swaminathan; Sen Gupta, Sayam (ACS CATALYSIS, 2024)
Keywords: Ball milling; solid-state C-H hydroxylation

Shola: a 3D porous hydrophobic-oleophilic lignocellulosic material for efficient oil/water separation - Mondal, Keya; Advani, Kushagra; Ghosh, Snigdha; Shanmugnathan, Kadhiravan; Kulsi, Goutam; Sivaram, Swaminathan; Sen Gupta, Sayam (Journal of Materials Chemistry A, 2025)
Transitioning from the fossil fuel era to a sustainable future requires increasing adoption of high-performing renewable materials in industrial applications. Natural polymers derived from lignocellulosic materials are often considered more environmentally friendly than their petroleum-based synthetic analogs. Aeschynomene aspera, commonly known as Shola, has been found to be a large source of amorphous cellulose and a useful sorbent for the removal of oil from water. The Shola pith, the pure white inner stem, is rich in cellulose and has an exquisite three-dimensional and hierarchical porous architecture created by nature. The pith consists of about 70 wt% cellulose as the main chemical component, which is much higher than what is found in other lignocellulosic sources. In addition, the pith has about 12 wt% hemicellulose, 2-3 wt% pectin, 10 wt% lignin, 2.5 wt% wax, and 2 wt% protein as other chemical components. It was observed that water has a high contact angle (135 degrees) on the surface of the pith, while oil droplets instantly spread on the surface, indicating excellent hydrophobic-oleophilic properties. Further studies reveal that the Shola pith exhibits a fast and high sorption capacity of 40-60 g/g for various oils and organic liquids. Silicone oil shows a sorption capacity of about 166 g/g. When applied to oil-floating-over-water, the Shola pith exhibits high selectivity for oil over water; almost all oil on the surface could be removed, leaving no trace of oil on the water surface. The Shola pith can also efficiently separate oil from an oil-in-water emulsion. This behavior is unprecedented in natural sorbents. The used material sorbs a considerable volume of the oil even after the 7th cycle. Furthermore about 95% of sorbed oil could be recovered from the material by solvent extraction. This study reveals for the first time some of the unique and interesting properties of Shola, a widely found biomass native to the eastern parts of the Indian subcontinent, and opens up possibilities of exploiting it for valuable applications.